1995
DOI: 10.1002/humu.1380050407
|View full text |Cite
|
Sign up to set email alerts
|

African, Native American, and European mitochondrial DNAs in Cubans from Pinar del Rio Province and implications for the recent epidemic neuropathy in Cuba

Abstract: Genetic predisposition, particularly specific mitochondrial DNA (mtDNA) backgrounds, has been proposed as a contributing factor in the expression of an epidemic of bilateral optic neuropathy that has affected residents of Cuba since 1991. To substantiate or refute the possibility that specific subsets of mtDNAs could participate in disease expression, we took advantage of the heterogeneous ethnic origin of the Cuban population and the recent identification of a number of mtDNA polymorphisms that appear to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…In these cases, the indigenous population was even more dramatically replaced by African slaves and to a certain extent by Europeans. Our results differ from a previous independent study carried out in the Cuban province of Pinar del Rio [36], whose authors estimated that 50% of maternal lineages in this province were of European, 46% African, and a maximum 4% of Native American origin. Our results indicate that the Native American mtDNA haplogroup patterns are statistically homogeneous across the island, the maternal Native American substrate being higher than 25% in all provinces.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In these cases, the indigenous population was even more dramatically replaced by African slaves and to a certain extent by Europeans. Our results differ from a previous independent study carried out in the Cuban province of Pinar del Rio [36], whose authors estimated that 50% of maternal lineages in this province were of European, 46% African, and a maximum 4% of Native American origin. Our results indicate that the Native American mtDNA haplogroup patterns are statistically homogeneous across the island, the maternal Native American substrate being higher than 25% in all provinces.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results indicate that the Native American mtDNA haplogroup patterns are statistically homogeneous across the island, the maternal Native American substrate being higher than 25% in all provinces. Specifically, in Pinar del Rio we detected 33% Native American maternal lineages, a figure that significantly contrasts (χ 2 = 12.32; 2 d.f., P = 0.002) with the 4% found in the study by Torroni [36]. This difference highlights the risk of population stratification that can easily show up in case-control disease association studies, for example, leading to an increase of the false positive rate [26,37].…”
Section: Discussionmentioning
confidence: 84%
“…23 However, an analysis of specimens from the case patients did not reveal any pathogenetic role for mitochondrial DNA mutations or for any specific mitochondrial genetic background. 24,25 We found that tobacco use, particularly cigar smoking, and high cassava consumption relative to total energy intake were both associated with an increased risk of optic neuropathy. In contrast, the risk was reduced among the subjects with higher serum concentrations of carotenoids and higher dietary intakes of nutrients from animal products and some B complex vitamins.…”
Section: Discussionmentioning
confidence: 86%
“…The modern Cuban population is a genetic admixture of European (mainly Spanish) settlers, Native Americans and Africans imported to compensate for the decline in population following Spanish conquest of the island in 1511. A recent study of mtDNA haplotypes confirmed this heterogeneous ethnic background of the Cuban population, revealing that around 50% of Cuban mtDNAs originated from Europeans, 46% from Africans and only 4% from Native Americans (Torroni et al 1995). In 1984 the Neonatal Screening Program for hyperphenylalaninemia began in all the Cuban provinces, analysing 1,516,300 samples through 1999.…”
Section: Introductionmentioning
confidence: 88%